Retinal Endothelial Function, Physical Fitness and Cardiovascular Risk: A Diagnostic Challenge - Streese, Lukas; Kotliar, Konstantin; Deiseroth, Arne; Infanger, Denis; Vilser, Walthard; Hanssen, Henner (Frontiers in Physiology, 2019)
Introduction: Dynamic retinal vessel analysis (DVA) is a new non-invasive method to quantify microvascular endothelial dysfunction by flicker light-induced dilatation (FID). FID has been shown to be impaired in type 2 diabetes as well as heart failure. The aim of the study was to analyze FID in healthy active versus healthy sedentary and cardiovascular (CV) risk patients in addition to corresponding static vessel diameters. Methods: Thirty-one healthy active (HA, mean age 60±8 years), 33 healthy sedentary individuals (HS, 59±7 years) and 76 sedentary patients with increased CV risk (SR, 58±6 years) were included in this cross-sectional study. Group differences in CV risk factors and cardiorespiratory fitness, maximal arteriolar (ADmax) and venular (VDmax) dilatation as well as the arteriolar (AFarea) and venular (VFarea) area under the flicker curve were analyzed. The central retinal arteriolar and venular diameters were used to calculate the arteriolar-to-venular diameter ratio (AVR). Results: HS [ADmax = 3.5 (2.1)%; AFarea = 48.2 (31.9)%*s] showed higher FID compared to SR [ADmax = 2.7 (1.8)%, p=0.021; AFarea = 34.5 (26.5)%*s, p=0.006] and HA [AFarea = 32.8 (23.1)%*s, p=0.029]. HA and SR did not significantly differ. HA had a higher AVR (0.87±0.05) compared to HS (0.83±0.04, p<0.001) with further deterioration in SR (0.79±0.05, p<0.001). Interestingly, 28 participants had impaired FID but normal AVR and 43 participants had normal FID but impaired AVR. Discussion: FID can differentiate between sedentary low and high risk individuals. However, FID in healthy active persons (HA) seemed impaired with a concomitant higher AVR. We postulate that lower FID in HA may be explained by predilatated arterioles and a reduced dilatation reserve. We recommend combination of FID with analysis of retinal vessel diameters to differentiate functional non-responders from manifest microvascular endothelial dysfunction and, thereby, improve microvascular risk stratification in a personalized medicine approach. Clinical Trial Registration: ClinicalTrials.gov: NCT02796976 (https://clinicaltrials.gov/ct2/show/NCT02796976)